Single dose of multi-clade virus-like particle vaccine protects chickens against clade 2.3.2.1 and clade 2.3.4.4 highly pathogenic avian influenza viruses - Yong-Myung Kang (Nature Portfolio, 2021)
Abstract Virus-like particles (VLPs) are recognized as an alternative vaccine platform that provide effective protection against various highly pathogenic avian influenza viruses (HPAIVs). Here, we developed multi-clade VLPs expressing two HAs (a chimera of clade 2.3.2.1c and clade 2.3.4.4c HA) within a single vector. We then compared its protective efficacy with that of a monovalent VLP and evaluated its potency against each homologous strain. Chickens vaccinated with the multi-clade VLP shed less virus and were better protected against challenge than birds receiving monovalent vaccines. Single vaccination with a multi-clade VLP resulted in 100% survival, with no clinical symptoms and high levels of pre-challenge protective immunity (7.6–8.5 log2). Moreover, the multi-clade VLP showed high productivity (128–256 HAU) both in the laboratory and on a large scale, making it cheaper than whole inactivated vaccines produced in eggs. However, the PD50 (protective dose 50%) of the multi-clade VLP against clades 2.3.2.1c and 2.3.4.4c was < 50 PD50 (28 and 42 PD50, respectively), and effective antibody response was maintained for 2–3 months. This multi-clade VLP protects against both clades of HPAI viruses and can be produced in high amounts at low cost. Thus, the vaccine has potential as a pandemic preparedness vaccine.